2011
DOI: 10.1111/j.1751-2980.2011.00517.x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between pancreatic carcinoma and mass‐forming chronic pancreatitis: Usefulness of high b value diffusion‐weighted imaging

Abstract: OBJECTIVE:To investigate the value of high b value diffusion-weighted (DW) imaging in differentiating between pancreatic carcinoma and mass-forming chronic pancreatitis (MFCP). METHODS:Fifty-one consecutive patients with pathology-proven pancreatic carcinoma (n = 37) or MFCP (n = 14) were evaluated with DW imaging (b value, 0 and 1000 s/mm 2 ) at a 3-T MR system. Overall 20 healthy volunteers were evaluated as the control group. The apparent diffusion coefficient (ADC) values of normal pancreas, pancreatic car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 35 publications
1
22
0
1
Order By: Relevance
“…Future well‐designed, multicenter studies are needed to better determine the most appropriate use of ADC in the area of pancreatic disease. Third, our DWI experiments were performed with a relatively low b value (600 s/mm 2 ) to minimize motion artifacts and to improve the SNR in pancreas, while it has been shown that the use of higher b values may be more sensitive to reflect true diffusion . Furthermore, only two b values (0 and 600 s/mm 2 ) were performed in our study to reduce inspection time in the clinical setting, although ideally multiple b values should be used for more accurate measurements of ADC values .…”
Section: Discussionmentioning
confidence: 99%
“…Future well‐designed, multicenter studies are needed to better determine the most appropriate use of ADC in the area of pancreatic disease. Third, our DWI experiments were performed with a relatively low b value (600 s/mm 2 ) to minimize motion artifacts and to improve the SNR in pancreas, while it has been shown that the use of higher b values may be more sensitive to reflect true diffusion . Furthermore, only two b values (0 and 600 s/mm 2 ) were performed in our study to reduce inspection time in the clinical setting, although ideally multiple b values should be used for more accurate measurements of ADC values .…”
Section: Discussionmentioning
confidence: 99%
“…Intravoxel incoherent motion (IVIM)‐derived parameters and apparent diffusion coefficient (ADC) have been proposed as imaging biomarkers for fibrosis and cell density in a number of conditions, including PAC. The majority of pancreas diffusion‐weighted imaging (DWI) studies have focused on normal pancreatic anatomic variations and function, detection and differentiating of pancreatitis from neoplasm or characterizing pancreatic masses . Few have prospectively investigated the underlying histopathology correlates for these observations, and only one used the IVIM model.…”
mentioning
confidence: 99%
“…The majority of pancreas diffusion-weighted imaging (DWI) studies have focused on normal pancreatic anatomic variations and function, [10][11][12] detection and differentiating of pancreatitis from neoplasm or characterizing pancreatic masses. [13][14][15][16][17][18][19][20][21][22][23][24][25] Few have prospectively investigated the underlying histopathology correlates for these observations, 22,[26][27][28] and only one used the IVIM model. In the IVIM study, moderate fibrosis was associated with lower diffusion (D) compared to severe fibrosis in contrast to previous studies that found a negative correlation between ADC 2b and dense fibrosis.…”
mentioning
confidence: 99%
“…Bununla birlikte MR teknolojisinde son zamanlarda yaşanan gelişmeler ile pankreasın malign ve benign lezyonlarının ayırımında etkin teknikler ortaya çıkmıştır. Yapılan çalışmalarda difüzyon ağırlıklı MR, kontrastlı MR, MR spektroskopi gibi tekniklerle inflamatuar lezyonların kanserden ayırımında sensitivite ve spesifite % 90'ların üzerine çıkabilmiştir 10,11 . FDG-pozitron emisyon tomografisi (PET)' nin pankreatik kanser ile kronik pankreatit ayırımında sensitivitesi BT veya MR' dan daha yüksek saptanmıştır.…”
Section: Sonuçunclassified